Exploring youth grassroots nationalism in Singapore : a case study of youth executive committees - Fatin Amira Mohamed Noor (2011)
Singapore’s national identity is inherently dynamic as seen from the State’s numerous and continuous efforts at developing a coherent and stable concept of the nation. However, studies have only looked at the State’s primary role in understanding the nature of Singapore’s national identity. Leveraging on Michel Foucault’s concept of discourse, power and governmentality, this research offers a more critical look at the construction of national identity in Singapore from below. I look at the local grassroots sector to understand the nature of the power relationship between the State and the sector which involves the conceptualisation of the nation. I argue that through grassroots volunteering, the members will be shown to have a more positive concept and identification to the nation. Although this may seem to indicate a successful top down influence of the State, this research also included a critical understanding of the micro-politics involved in the construction of national identity.